Strategi Penanaman Karakter Peduli Sosial Anak - Firdaus, Umi Risatul; Putro, Khamim Zarkasih (Annual Conference on Islamic Early Childhood Education (ACIECE), 2024)
Social awareness is a character that needs to be developed from an early age, because a large number of kids exhibit social apathy. Children can develop their personalities to suit their social environment through character education. Thus the purpose of this study is to examine the nature of social care, by identifying strategies that are appropriate for early childhood. This research combines qualitative descriptive methodology with textual analytical techniques or literature study. The literature used must be in Indonesia and have been published within the previous five years in the form of essays examining the nature of social concern. Data reduction, data visualization, and data review as data analysis. The results of the research conclude that providing knowledge, instilling confidence and direct action are three strategies used to instill children’s character, especially social care. Developing socially aware children from an early age requires learning strategies that meet children’s needs and collaboration between teachers and parents to ensure continuty in instilling children’s character.